Origins of Nikolay Pokrovsky’s Ideas on the Subject and Tasks of Christian Archeology and His Own Discoveries - Buzykina, Yulia N. (Actual Problems of Theory and History of Art, 2023)
The aim of the article is to reveal the sources Nikolay Pokrovskiy’s ideas about the subject and tasks of Christian archeology, formulated by him for the course of Christian archeology and his master’s thesis The Origins of the Ancient Christian Basilika. The analysis of the text of the introductory lecture of Professor F. X. Kraus on Christian archeology, which Pokrovsky heard during his studies abroad, allows to conclude that Kraus had a serious influence on the Russian scientists with his views on the subject of Christian archeology. Pokrovsky also recognizes Christian archeology as an auxiliary historical discipline, but unlike the German scholar, places this discipline within the framework of history, not theology. Both recognize monuments, including works of art, as the subject of their discipline. The study of national antiquities, only touched upon by F. X. Kraus, became of fundamental importance to Pokrovsky, since the Christian antiquities of Russia were very poorly studied and therefore had a huge research potential. Since the methodological basis for the publication of numerous materials on Russian antiquities was weak, Pokrovsky pays special attention to the methodology of description and the analysis of monuments, which should be aimed at identifying the typical features of phenomena and their genesis, which he demonstrated in his dissertation, although using different material.
Keywords: Nikolay Pokrovsky; Franz Xaver Kraus; Christian archeology; history of science; art historians; theorists of art